USM FOUNDATION RAISES CLOSE TO RM3 MILLION TO HELP POOR STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Universiti Sains Malaysia Foundation (USM Foundation) will organise four charity programmes this year to raise funds for the various ‘Tabung’ (Fund) set up under the Foundation to help advance the strategic priorities of the University for the benefit of its community.